Financial attractiveness of investing in «bee houses» within U.S. wellness zones - Misiats, Oleksandra (Здобутки економіки: перспективи та інновації, 2025)
The relevance of the research is determined by the growing role of nature-oriented investments within the framework of sustainable development and the transition of the tourism and recreation industry of the United States of America (USA) toward environmentally responsible business models. Under conditions of increasing demand for wellness tourism and biobased products, investments in the construction of beehives are considered an innovative way to combine profitable activity with environmental and social benefits. Purpose of the article: to define the economic essence, structural components, and practical conditions for forming the financial attractiveness of investments in the construction of bee houses in the wellness zones of the USA as a promising direction for the development of environmentally oriented and health-improving tourism. Methods. The study employs systemic, structural-functional, and comparative approaches, which enable a comprehensive assessment of the investment attractiveness of this sector. Methods of economic analysis, cash flow modelling, and content analysis of regulatory and institutional sources were employed to identify the key factors influencing the financial efficiency of such projects. Results. The content and structure of investment attractiveness in nature-based projects have been analysed, and the influence of market, technological, locational, and financial–institutional factors on the profitability of bee house initiatives has been demonstrated. The primary development barriers have been identified: regulatory fragmentation, a shortage of long-term financing, a personnel deficit, and informational asymmetry. The integration potential of bee houses within local economies, tourism infrastructure, and environmental programs has been assessed, proving their ability to generate a multiplier socio-economic effect. Conclusions. It has been established that the development of investments in bee houses contributes to forming a new paradigm of sustainable tourism, within which profitability is combined with environmental and social efficiency. The necessity of regulatory unification, expansion of financial incentives, development of public–private partnerships, and institutional support for eco-projects has been substantiated. Future studies should focus on the quantitative modelling of risks and profitability of nature-oriented investments, the development of indicators for social and environmental returns, and the creation of an analytical base for strategic management of sustainable investment flows in the tourism sector.